ISLAMIC VS CONVENTIONAL FUNDS WITHIN THE FAMILY: SELECTIVITY SKILLS AND MARKET TIMING ABILITY - Anas Ahmad Bani Atta; Ainulashikin Marzuki (Bank Indonesia, 2020)
ABSTRACT The aim of the study is to compare the performance of Islamic mutual fund (IMF) and conventional mutual fund (CMF) within the same family, in addition, to examine the performance of fund family in Malaysia for the period from 2007 to 2018. The study used eight measures of performance, raw returns, excess returns, Sharpe ratio, Treynor ratio, Jensen alpha, Carhart four-factor model as selectivity models, In addition to Treynor & Mazuy (TM) and Hendrickson & Merton (HM) as market timing models. The study contributes by investigating and compares the performance at the family level. The results reported that IMFs exhibited some fund selection ability over CMFs. However, both types of funds displayed poor market timing ability. At a fund family level, the results show the fund families exhibited good fund selections skills, at the same time, fund family still exhibited poor market timing ability. The novel result of this study that the difference in performance between Islamic and conventional funds shrank compared to the results of previous studies. Due to the common advantages offered by the families for both types of funds. The findings are important to investors because the results provide new evidence about the fund families' performance. Most investors follow the top-down approach, where mutual fund investors initially choose fund families before deciding which funds to hold. In addition, the results are important for managers to decide which types of funds that they may issue in their own families, so that they can perform well in the future.